In vivo B 1 + enhancement of calf MRI at 7 T via optimized flexible metasurfaces - Jacobs, Paul S; Wilson, Neil; Brink, Wyger; Swain, Anshuman; Armbruster, Ryan; Hanumapur, Aniketh; Tisdall, M Dylan; Detre, John; Nanga, Ravi Prakash Reddy; Elliott, Mark A; Reddy, Ravinder (Magnetic resonance in medicine, 2024)
Ultrahigh field (≥7 T) MRI is at the cutting edge of medical imaging, enabling enhanced spatial and spectral resolution as well as enhanced susceptibility contrast. However, transmit ( ) field inhomogeneity due to standing wave effects caused by the shortened RF wavelengths at 7 T is still a challenge to overcome. Novel hardware methods such as dielectric pads have been shown to improve the field inhomogeneity but are currently limited in their corrective effect by the range of high-permittivity materials available and have a fixed shelf life. In this work, an optimized metasurface design is presented that demonstrates in vivo enhancement of the field. A prototype metasurface was optimized by an empirical capacitor sweep and by varying the period size. Phantom temperature experiments were performed to evaluate potential metasurface heating effects during scanning. Lastly, in vivo gradient echo images and maps were acquired on five healthy subjects on a 7 T system. Dielectric pads were also used as a comparison throughout the work as a standard comparison. The metasurfaces presented here enhanced the average relative SNR of the gradient echo images by a factor of 2.26 compared to the dielectric pads factor of 1.61. Average values reflected a similar enhancement of 27.6% with the metasurfaces present versus 8.9% with the dielectric pads. The results demonstrate that metasurfaces provide superior performance to dielectric padding as shown by maps reflecting their direct effects and resulting enhancements in image SNR at 7 T.